Effects of rations and seasons on milk yield and composition in small and medium dairy farms from a Tunisian northern area (Bizerte Region) - Khaoula Attia; Cyrine Darej; Naceur M’Hamdi; Ghazi Sadkaoui; Nizar Moujahed (Mljekarstvo)
In Tunisia, dairy farming faced several problems limiting the improvement of the milk sector, mostly at the level of small farmers. These difficulties are related to the milk quality affected by the feed quality distributed throughout the year. This study aimed to evaluate the effect of rations and seasons on daily individual milk production (DIMP) and some physicochemical characteristics (Fat content: FC, Protein content: PC, Urea concentration: UC, Total Solids: TS). A survey and milk samplings were performed on 135 farmers. Collected data were treated by the variance analysis using the GLM procedure of the SAS system. This study allowed to identify four types of ration: TR1: Concentrate (CC)+Green Forage(GF), TR2: CC+Dry Forage (DF), TR3: CC+GF+DF and TR4: Diet containing Silage (S), used by farmers with the frequencies of 14.82, 37.19, 44.6 and 3.38% respectively. The highest DIMP (P<0.0001) was obtained by TR1 (17.3 kg/day) and the lowest (13.6 kg/day) by TR2. TR4 allowed FC, PC (P<0.05) and TS (P<0.01) higher (3.84, 3.14 and 12.31% respectively) than those obtained in the other rations. The UC (P<0.0001) was the highest in TR1 and TR3 (32.05 mg/dL) followed by TR4 (28.3 mg/dL) and TR2 (26.2 mg/dL). Concerning the season effect, the highest DIMP (P<0.0001) was obtained during spring (17.7 kg/day), the lowest was during autumn (13.1 kg/day). The FC (P<0.05) was the lowest in winter (3.52%). The PC (P<0.01) was higher during autumn and winter (averaged 3.07%). The UC (P<0.0001) was the highest in spring (32.23 mg/dl) and the lowest in autumn (25.67 mg/dL). It was concluded that milk parameters were in the acceptable ranges comparatively to the national averages.